2014
DOI: 10.2478/hukin-2014-0114
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Stress Urinary Incontinence in Elite Female Endurance Athletes

Abstract: The goal of the study was to assess the prevalence of stress urinary incontinence in a group of elite female endurance athletes, as professional sport is one of the risk factors for stress urinary incontinence. SUI rates in the groups of female cross-country skiers and runners were compared to determine whether the training weather conditions like temperature and humidity influenced the prevalence of urinary incontinence. An anonymous questionnaire was distributed among 112 elite female athletes ie., 57 cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 16 publications
2
26
1
10
Order By: Relevance
“…32 On the other hand, Yi et al 13 found that 24% of tri-athletes had at least one arm of the female athlete triad, but the athletic triad was not associated with symptoms of any pelvic floor disorders, for example, UI. Our results did not confirm other findings from other sports where low BMI 12,29 and length of participation in sport/hours of training 15,18,[33][34][35][36][37][38][39][40][41][42][43] were significant risk factors. This may be explained by the high training load and low BMI in all the rhythmic gymnasts.…”
Section: Discussioncontrasting
confidence: 99%
“…32 On the other hand, Yi et al 13 found that 24% of tri-athletes had at least one arm of the female athlete triad, but the athletic triad was not associated with symptoms of any pelvic floor disorders, for example, UI. Our results did not confirm other findings from other sports where low BMI 12,29 and length of participation in sport/hours of training 15,18,[33][34][35][36][37][38][39][40][41][42][43] were significant risk factors. This may be explained by the high training load and low BMI in all the rhythmic gymnasts.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the recommendations, items 9, 17, and 21 stood out as they were not present in any of the 5 articles included in the review. These were: describe any efforts to address potential sources of bias (9); report other analyses done (17); discuss the generalizability (external validity) of the study results (21).…”
Section: Resultsmentioning
confidence: 99%
“…Literature proves that sports practice of high impact is related to the occurrence of pelvic floor dysfunctions, such as UI [21][22]. Reis et al [13] affirms that among the sports modalities of high impact, volleyball belongs to the ones that most intensively exert a direct influence on the pelvic floor of the athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos compararam a prevalência de IU entre atletas e não atletas, e concluiram que atletas de elite têm alta prevalência de IU quando comparadas a um grupo controle, e ainda que, na prática de esportes de alto impacto, o risco aumenta 12,23,27,[30][31][32] . Já Salvatore et al 33 , ao analisar atletas recreacionais, observaram que a incidência de IU entre as mulheres era menor, e concluíram que o impacto da incontinência urinária nas atletas recreacionais não é tão significativo quando comparado com a prática esportiva profissional.…”
Section: Prevalência De Iuunclassified